Differential Signature of the Microbiome and Neutrophils in the Oral Cavity of HIV-Infected Individuals - Perez Rosero, Eliana; Heron, Samantha; Jovel, Juan; O’Neil, Conar R.; Turvey, Shannon Lee; Parashar, Pallavi; Elahi, Shokrollah (Frontiers in Immunology, 2021)
HIV infection is associated with a wide range of changes in microbial communities and immune cell components of the oral cavity. The purpose of this study was to evaluate the oral microbiome in relationship to oral neutrophils in HIV-infected compared to healthy individuals. We evaluated oral washes and saliva samples from HIV-infected individuals (n=52) and healthy controls (n=43). Using 16S-rRNA gene sequencing, we found differential -diversity using Principal Coordinate Analysis (PCoA) with Bray-Curtis distances. The -diversity analysis by Faith’s, Shannon, and observed OTUs indexes indicated that the saliva samples from HIV-infected individuals harbored significantly richer bacterial communities compared to the saliva samples from healthy individuals. Notably, we observed that five species of Spirochaeta including Spirochaetaceae, Spirochaeta, Treponema, Treponema amylovorum, and Treponema azotonutricum were significantly abundant. In contrast, Helicobacter species were significantly reduced in the saliva of HIV-infected individuals. Moreover, we found a significant reduction in the frequency of oral neutrophils in the oral cavity of HIV-infected individuals, which was positively related to their CD4+ T cell count. In particular, we noted a significant decline in CD44 expressing neutrophils and the intensity of CD44 expression on oral neutrophils of HIV-infected individuals. This observation was supported by the elevation of soluble CD44 in the saliva of HIV-infected individuals. Overall, the core oral microbiome was distinguishable between HIV-infected individuals on antiretroviral therapy compared to the HIV-negative group. The observed reduction in oral neutrophils might likely be related to the low surface expression of CD44, resulting in a higher bacterial diversity and richness in HIV-infected individuals.